2020
DOI: 10.29278/azd.655226
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between fruit size and picking scar size in some organically grown highbush blueberries (Vaccinium corymbosum L.)

Abstract: This study was carried out to determine the correlation between fruit size and picking scar diameter of organically grown northern highbush blueberry cultivars. In the experiment, eight northern highbush blueberry cultivars (Toro, Brigitta, Darrow, Patriot, Bluecrop, Bluegold, Bluejay and Chandler) (Vaccinium corymbosum L.), have five years old plants and grows in Trabzon conditions, were used. The differences in the fruit size and the picking scar diameter among the cultivars, and the annual differences withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The increment in TPC of yoghurts with the addition of different fruits have been observed in many studies (Demirkol & Tarakci 2018). Previous studies in the literature found that the blueberry had strong antioxidant activity (Çelik et al 2013, Liu & Lv 2019, Saral et al 2015, Tagliani et al 2019.…”
Section: Dpph Radical Scavenging Activity and Tpc Of Blueberry Added ...mentioning
confidence: 91%
See 2 more Smart Citations
“…The increment in TPC of yoghurts with the addition of different fruits have been observed in many studies (Demirkol & Tarakci 2018). Previous studies in the literature found that the blueberry had strong antioxidant activity (Çelik et al 2013, Liu & Lv 2019, Saral et al 2015, Tagliani et al 2019.…”
Section: Dpph Radical Scavenging Activity and Tpc Of Blueberry Added ...mentioning
confidence: 91%
“…These results were in agreement with the results of the present study. Previous studies in the literature found that the blueberry showed strong antioxidant activity (Çelik et al 2013, Liu & Lv 2019, Tagliani et al 2019. On the other hand, phenolic compounds such as anthocyanins decomposed in the beginning of the storage period and later gained stability (Wallace & Giusti 2008).…”
Section: Dpph Radical Scavenging Activity and Tpc Of Blueberry Added ...mentioning
confidence: 97%
See 1 more Smart Citation